Decentralization of Local Government Authority to Village Governments in Domestic Waste Management: A Case Study of Temanggung Regency - Aria Wirawan; Maryono Maryono; Kismartini Kismartini (School of Postgraduate Studies, Diponegoro Univer, 2025)
Waste management is a major environmental challenge in Indonesia. With the increasing volume of waste due to urbanization and population growth, waste management capacity is limited. This research explores the Temanggung district government's efforts to implement a decentralized waste management policy involving village governments and communities. Through the policy that started in 2019, waste management coverage increased significantly from 30.7% in 2018 to 70.9% in 2023, with villages playing an active role in waste reduction. This research uses in-depth interviews, observation, and document review methods to understand the decentralization policy's implementation process and the challenges faced in its implementation. The results show that decentralization contributes to improving the effectiveness of waste management in Temanggung and can be an alternative solution to be implemented in other regions in Indonesia.